2023
DOI: 10.3390/ijerph20053796
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spring Barley Fertilization on the Content of Polycyclic Aromatic Hydrocarbons, Microbial Counts and Enzymatic Activity in Soil

Abstract: Soil-dwelling microorganisms play an important role in the environment by decomposing organic matter, degrading toxic compounds and participating in the nutrient cycle. The microbiological properties of soil are determined mainly by the soil pH, granulometric composition, temperature and organic carbon content. In agricultural soils, these parameters are modified by agronomic operations, in particular fertilization. Soil enzymes participate in nutrient cycling and they are regarded as sensitive indicators of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…The lyophilization process itself has no data that can affect the formation of PAH, since the amount of PAH detected is exceptionally higher only when using brewery by-products. Ewa Mackiewicz-Walec et al study has shown that weather conditions and microbial activity can cause large seasonal variations in PAH levels during barley cultivation [99]. Therefore, we can cautiously put forward the following hypothesis that in barley used for beer production and in its biowaste-barley malting used as a substrate for the larvae-higher amounts of PAH were formed due to the growing conditions, compared to LWYG, LWYP, and LWYC.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 96%
“…The lyophilization process itself has no data that can affect the formation of PAH, since the amount of PAH detected is exceptionally higher only when using brewery by-products. Ewa Mackiewicz-Walec et al study has shown that weather conditions and microbial activity can cause large seasonal variations in PAH levels during barley cultivation [99]. Therefore, we can cautiously put forward the following hypothesis that in barley used for beer production and in its biowaste-barley malting used as a substrate for the larvae-higher amounts of PAH were formed due to the growing conditions, compared to LWYG, LWYP, and LWYC.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 96%